Rola badań marketingowych na rynku agrarnym - Nogieć, Joanna (Role of Marketing Research on the Agrarian Market, 2006)
The article shows the short characterization of the agrarian sector, presents the segmentation of farming producers. It lets describe the specific character of this market. The examples of realized research marketing, such as the description of chosen segments of farming producers, the description of communication channels are presented. The article shows what role the marketing research plays in the agrarian section, especially in the environment.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1107, s. 454-459